Association between anxiety and sleep quality in the General Surgery residents of Udayana University - Ida Bagus Gede Wisnu Wardhana; Cokorda Bagus Jaya Lesmana; Luh Nyoman Alit Aryani; Wayan Westa; I Gusti Ayu Endah Ardjana; Ni Ketut Sri Diniari (Journal of Clinical and Cultural Psychiatry, 2020)
Background: Sleep quality not only affects physical health but also on individual performance. Anxiety is thought to associate with poor sleep quality. This study aims to determine the association between anxiety and sleep quality in surgery residents of Faculty of Medicine, Udayana University. Methods: The subjects of the study were 48 surgery residents of Faculty of Medicine of Udayana University. The study used a cross sectional analytical method. Measurement of anxiety using the Beck Anxiety Inventory (BAI) and sleep quality questionnaire using the Pittsburgh Sleep Quality Index (PSQI). Data were analyzed descriptively and used the chi square test with significance level p <0.05. Results: The results showed that 33.3% of surgery residents of Faculty of Medicine of Udayana University had anxiety and most had poor sleep quality (87.5%). There is an association between anxiety and sleep quality in surgery residents of Faculty of Medicine of Udayana University with PR 3.0 (95% CI 0,9-9,1; p <0.005). Conclusion: This study shows that there is a significant relationship between anxiety and sleep quality where surgery residents of Faculty of Medicine of Udayana University with anxiety 3 times at risk of developing poor sleep quality than those without anxiety. Therefore it is necessary to manage anxiety as well as the arrangement of night shift to improve sleep quality.